The effects of music and the time-of-day on cognitive abilities of tennis player. Issue 3 (4th May 2019) - Jarraya, Sana; Jarraya, Mohamed
Abstract : While the effect of music on the physical performance of athletes has been investigated at a large scale, there is noticeable lack of information about its effect on their cognitive performance. The purpose of this investigation was to assess the effects of listening to music and the time-of-day on cognitive abilities of Tunisian tennis players in terms of reaction time (RT), attention, executive functions and spatial memory skills. Fourteen Tunisian tennis players (17 ± 1.2 years, 172 ± 6.23 cm, 70.15 ± 5.31 kg, level of experience: 9.2 ± 1.3 years) participated in the study. Four test sessions were performed at the following times of day: two in the morning (7:00 am–9:00 am) and two in the evening (5:00 pm–7:00 pm). During each session, subjects performed RT test, the barrage test, the trail-making test and the paper-folding test, either without music or immediately after 10 min of listening. The oral temperature was taken at the beginning of each session. The main finding was that cognitive performances of Tunisian tennis players are time-of-day dependent with an improvement from the morning to the evening. Furthermore, listening to music before performing cognitive tasks enhances cognitive performances if it is compared with no music condition. Thus, Tunisian tennis players are advised to train in the evening with music on primarily during warm-up and/or during recovery time to boost cognitive parameters which in turn positively influence motor response.